Analisis Kejiwaan Tokoh Dan Nilai Pendidikan Karakter Dalam 5 Dongeng Anak Dunia Karya Dedik Dwi Prihatmoko - Ismanto Ismanto (Universitas Palangka Raya, 2024)
Study This aim For describe aspect mental characters and the educational value of characters in fairy tales. This research is a qualitative descriptive research with content analysis method (content analysis). The literary psychology approach used is theory psychology David Krech. The research data sources are: (1) Text 5 Fairy Tales Children of the World by Dedik Dwi Prihatmoko, (2) relevant literature books. Technique collection data with technique read And technique write. Technique validation data with triangulation data And source. Technique analysis data with model analysis interactive. Based on results analysis can concluded that: (1) There is aspect mental in theory psychology literature that emphasizes the emotional condition of each character in the fairy tale child by Dedik Dwi Prihatmoko. The psychological theory used is theory according to David Krech which is divided into four, including emotions basic, emotions related to self-evaluation, emotions that related to sensory stimulation, and emotions related to person other. (2) 5 Fairytale Child World work Dedik Bi Prihatmoko load mark education character based on Profile Student Pancasila. Found mark moral glorious, diversity global, mutual cooperation, independent, creative and critical reasoning. (3) 5 World Children's Tales by Dedik Bi Prihatmoko worthy used by Teacher For develop students' reading ability and provide an understanding of emotions And mark kind.